2014
DOI: 10.1111/acer.12554
|View full text |Cite
|
Sign up to set email alerts
|

Choline Partially Prevents the Impact of Ethanol on the Lipid Raft Dependent Functions of L1 Cell Adhesion Molecule

Abstract: Background Fetal Alcohol Spectrum Disorder, the leading known cause of mental retardation, is caused by alcohol exposure during pregnancy. One mechanism of ethanol teratogenicity is the disruption of the function of L1 cell adhesion molecule (L1). These functions include enhancement of neurite outgrowth, trafficking through lipid rafts, and signal transduction. Recent data have shown that choline supplementation of rat pups reduces the effects of ethanol on neurobehavior. We sought to determine if choline coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
(85 reference statements)
0
17
0
Order By: Relevance
“…However, choline's effects are not necessarily restricted to these brain regions. An in vitro study using cultured, neonatal rat cerebellar granule cells showed some amelioration of EtOH‐induced molecular disruption of neurite outgrowth and signal transduction by pretreatment with choline; however, these were not restored to non–EtOH‐exposed, baseline levels (Tang et al., ). Of potential concern, there were several genes that were down‐regulated ( Setdb1 , G9a , and Dnmt1 ) or up‐regulated ( Dnmt3a ) in EtOH‐exposed subjects treated with choline when compared to nonexposed controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, choline's effects are not necessarily restricted to these brain regions. An in vitro study using cultured, neonatal rat cerebellar granule cells showed some amelioration of EtOH‐induced molecular disruption of neurite outgrowth and signal transduction by pretreatment with choline; however, these were not restored to non–EtOH‐exposed, baseline levels (Tang et al., ). Of potential concern, there were several genes that were down‐regulated ( Setdb1 , G9a , and Dnmt1 ) or up‐regulated ( Dnmt3a ) in EtOH‐exposed subjects treated with choline when compared to nonexposed controls.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, pre-exposure with choline protects against ethanol-related disruptions in lipid rafts (Tang et al, 2014). So in addition to changes in gene expression and cholinergic functioning, choline can lead to long-lasting changes in cell membranes and lipid homeostasis that will ultimately affect cell survival and signaling.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that choline supplementation of tissue culture media prior to ethanol exposure significantly ameliorates the effects of an acute ethanol exposure on L1-dependent neurite outgrowth and lipid raft- dependent signaling in cultured rat cerebellar granule neurons (30). However, previous studies on the effect of choline supplementation on rat behavior used choline supplementation with or after exposure to ethanol which did not match the experimental design of our biochemical studies (19; 20; 24-28).…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro model of cerebellar granule neurons, ethanol decreases L1 cell adhesion molecule (L1)-dependent neurite outgrowth and downstream signaling (30-32). Supplementation with choline prior to ethanol exposure shows improved neurite outgrowth and signaling in the presence of ethanol (30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation